Análisis comparativo del precio contrato y precio real del banano del 2015 - 2016 de la Asociación 3 de Julio. - Davila Ramirez, Carol Elizabeth (2017)
This paper is addressed to the comparative analysis of the contract price and the actual price of the box of bananas in the year 2016, and 2015 in the Association "July 3"; obstacles, the competitors involved in the activity, since the province of gold is mostly banana and its population in general of this trade-dependent directly or indirectly; In addition that the banana is the second most exported product after oil, and generates large revenues in foreign exchange to our country, in which we can give us there that it has been very beneficial both for the province as a national level through its figures and percentages establishing actual data. For e development of this analysis was the dissertation to definitions and conceptualizations of the object of study where they encounter issues that are directly related to the real issue of prices and contract prices to the box of bananas, the supply and demand in international markets and their impact on the sector. There are also the general aim and specifics that are what you want to achieve with this work that I mention the notable facts of because it is a fruit that consumed it in such developed countries and interest on marketing in export and the factors that influence the price of the box of bananas, and the country demanding customers of our sought-after fruit. Then comes the epistemological approach where the history of the banana is exposed and as it was giving over the years developing export and their problems had to address together with the number of clusters and after cases exported from its beginnings in the activity and how formalized the official minimum price of banana box. We determined with legal basis who is responsible for governing the sector Ministry and what trade policies that Ecuador has to facilitate the negotiations on export of fruit and strategies to expand into new markets. In the methodological process used to study guided by some scientific articles that we apply the method of documented research based on the sources of files provided by the company as well as the collection of information, in this case was necessary to sample with the producers that we conducted a survey and administrative staff an interview to confirm what is reflected in papers because the study was made to the Association through their purchases of fruit producers and sell it to the international market as well as the collection process was we needed a plan of collecting relevant data for research that will help us in the development of research and every step to arrive at a correct result; then in categorization is to know the categories that we organize ourselves to its drafting and support of analysis exhibiting tools, methods and techniques applied and how and how the sample was calculated to reach results and already with data collected were the respective comparisons and tabulations to which was demonstrated through statistical graphs which allows us to demonstrate the information obtained; later is was able to compare the deductions through the investigation process has been completed with the objectives proposed at the beginning of this analysis; data that were relevant to the construction of the conclusions and the respective recommendations, important part of the closure of our study.